ISOLATION AND CHARACTERISTIC OF NITROGEN-FIXING BACTERIA AND PHOSPHATE-SOLUBILIZING BACTERIA FROM SOIL HIGH IN MERCURY IN TAILINGS AND COMPOST AREAS OF ARTISANAL GOLD MINE - Nuraini, Yulia; Arfarita, Novi; Siswanto, Bambang (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2015)
The research was conducted at Brawijaya University and West Nusa Tenggara, from March 2013 to October 2013. The tailings areas of the gold mine contains high mercury (Hg) as much as 1,090 ppm, and living microbes (resistance) exist in a small number in such a condition. Microbial P solvents encountered came from the genus Bacillus with a population of 23 x 103 cfu g-1 and N-fixing bacteria encountered are of the genus Bacillus, with a population of 4 x 103 cfu g-1. Identification of species using Becton Dickinson Phoenix test, both species belong to Bacillus megaterium and Bacillus pumilus. While the waste corn and peanuts that has been composted for 4 weeks acquired P-solubilizing bacteria, such as Enterobacter, Bacillus and Pseudomonas, and N-fixing bacteria found was Pseudomonas and Azotobacter. While testing the activity and antagonism of N-fixing and P-solubilizing bacteria, the result on agar media did not show antagonism in its growth. Bacillus pumilus and Bacillus megaterium effective at 5 % molasses medium with the number of 0.15 x 1012 on seven days of incubation.Â Keywords: N-fixing bacteria, P-solubilizing bacteria, mercury, phytoremediation